Risk taking and sharing when risk exposure is interdependent - Abigail Barr; Trudy Owens; Ashira Perera (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2017)
Using a specially designed experiment, we investigate whether and how interdependence in risk exposure i.e., risk taking by some members of a potential risk sharing group affecting not only their own but also their co-members risk exposure, affects both risk taking and ex post sharing. The experimental subjects were Sri Lankan small-holders who face interdependent risk and share when neighbors fall on hard times in everyday life. We find that the Sri Lankan farmers reward socially responsible risk taking and, under some circumstances, punish socially irresponsible risk taking. Their behaviour is consistent with socially responsible risk taking being cost dependent, although, here, the statistical evidence is inconclusive. Finally, social responsibility in risk taking and ex post sharing do not appear to be substitutes, rather, they appear to be co-determined.
Keywords: C93; D81; O12; 330; behavioural experiment; risk-sharing; solidarity